Glass fiber reinforced concrete (GFRC) - strength and stress strain behavior for different grades of concrete - Kumar Poloju, Kiran; Rahul, Chiranjeeevi; Anil, Vineetha (International Journal of Engineering and Technology, 2018)
Concrete is a frail building material in strain. Characteristically, because of variety in temperature small cracks will be available in concrete. In addition, solid experiences low rigidity, constrained flexibility and little protection from splitting. Plain concrete will create splits because of plastic shrinkage, drying shrinkage and different reasons also .The advancement of these small scale breaks causes flexible miss happen-ing in concrete. The solid with no fiber is considered as fragile and feeble material. Related to glass fiber use there lies numerous techno efficient inquiries that settles on the decision of GFRC over strengthened cement troublesome. This paper exhibits the change in the mechan-ical quality properties and flexibility properties of Glass Fiber Reinforced Concrete. An Experimental program was done with and without utilizing glass fiber in various rate 0 to 0.09 percentages in conventional concrete keeping in mind the end goal to enhance the mechanical properties, stretch strain conduct and arrangement of splits. In light of the outcomes acquired from the trial comes about the conclusion is that both fiber and cementitious lattice can hold their physical and substance properties and they deliver a blend of properties that can't be accomplished when these segments are acting alone.Â Â